Acute Lymphoblastic Leukemia Cells Inhibit the Differentiation of Bone Mesenchymal Stem Cells into Osteoblasts In Vitro by Activating Notch Signaling. (3rd August 2015) - Yang, Gui-Cun; Xu, You-Hua; Chen, Hong-Xia; Wang, Xiao-Jing
Abstract : The disruption of normal hematopoiesis has been observed in leukemia, but the mechanism is unclear. Osteoblasts originate from bone mesenchymal stem cells (BMSCs) and can maintain normal hematopoiesis. To investigate how leukemic cells inhibit the osteogenic differentiation of BMSCs and the role of Notch signaling in this process, we cocultured BMSCs with acute lymphoblastic leukemia (ALL) cells in osteogenic induction medium. The expression levels of Notch1, Hes1, and the osteogenic markers Runx2, Osteopontin (OPN), and Osteocalcin (OCN) were assessed by real-time RT-PCR and western blotting on day 3. Alkaline phosphatase (ALP) activity was analyzed using an ALP kit, and mineralization deposits were detected by Alizarin red S staining on day 14. And then we treated BMSCs with Jagged1 and anti-Jagged1 neutralizing Ab. The expression of Notch1, Hes1, and the abovementioned osteogenic differentiation markers was measured. Inhibition of the expression of Runx2, OPN, and OCN and reduction of ALP activity and mineralization deposits were observed in BMSCs cocultured with ALL cells, while Notch signal inhibiting rescued these effects. All these results indicated that ALL cells could inhibit the osteogenic differentiation of BMSCs by activating Notch signaling, resulting in a decreased number of osteoblastic cells, which may impair normal hematopoiesis.